(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
Migration processes have already become an integral part of the development strategy of countries in the process of transforming modern international relations. Labor migration is a key migration trend that has a strong impact on development. Educational migration is another area that experts pay attention to. Both migration trends should be analyzed through many factors, among which "sustainable development" as a theoretical approach is of great importance. This article is aimed at an attempt to conduct such a study to study the use of the combined human and labor potential of states, create an appropriate regulatory framework, form a common labor market at the regional level, take coordinated measures aimed at regulating common problems of national labor markets with priority attention to protection all rights and freedoms of migrant workers. In this context, it is necessary to turn to sustainable development as a new approach of the UN and experts within the framework of a common development concept. It is also important to study the relationship between migration and development through the lens of the 17 Sustainable Development Goals (SDGs). Although the 17 SDGs do not directly address migration issues, their interrelation is important for understanding many processes of sustainable development. It is also important to understand the role of labor and educational migrants themselves as the main participants in the migration process, their contribution both to the host state through the results of labor and cultural aspects, and to the countries of origin through remittances, acquired skills and new knowledge. The pandemic has exacerbated the situation of migrants around the world, but at the same time has shown that even in such conditions, migrants contribute to the development of their countries. Thus, labor and educational migration in the post-pandemic period can become an enhanced driver of sustainable development. Key words: sustainable development, 17 SDGs, migration and development, educational migration and SDGs.